Export Performance and Competitiveness of Indonesian Food Commodities - Firmansyah, Firmansyah; Widodo, Wahyu; Karsinah, Karsinah; Oktavilia, Shanty (JEJAK: Jurnal Ekonomi dan Kebijakan, 2017)
The developments of the world trade requires the improvement of the competitiveness of products, including agricultural commodities. At the regional level, Indonesia’s agricultural commodities face the ASEAN free market competition. This study aims to identify and examine the competitiveness of Indonesian exports of several agricultural commodities in the international market by employing the index of competitiveness of trade specialization by trade specialization index (TSI), and the index of market penetration, by revealed comparative advantage (RCA). This study observed the HS 4 digit agricultural commodities, along 2011-2015. The study finds that the index of commodity trade specialization of estate crops sub-sector is in a stage of maturation of the world trade, or it has a very strong competitiveness. The food crops sub-sector stand on the introduction stage of the world trade or it has low competitiveness, or in other words, Indonesia is a net importer of the sector commodities. Although some of commodities have the strong competitiveness, but on the other hand, they do not have a strong comparative advantage. This is shown by the RCA value that less than 1. It means that a part of agricultural commodities, namely food crops, horticulture and estate, are still import oriented.The developments of the world trade requires the improvement of the competitiveness of products, including agricultural commodities. At the regional level, Indonesia’s agricultural commodities face the ASEAN free market competition. This study aims to identify and examine the competitiveness of Indonesian exports of several agricultural commodities in the international market by employing the index of competitiveness of trade specialization by trade specialization index (TSI), and the index of market penetration, by revealed comparative advantage (RCA). This study observed the HS 4 digit agricultural commodities, along 2011-2015. The study finds that the index of commodity trade specialization of estate crops sub-sector is in a stage of maturation of the world trade, or it has a very strong competitiveness. The food crops sub-sector stand on the introduction stage of the world trade or it has low competitiveness, or in other words, Indonesia is a net importer of the sector commodities. Although some of commodities have the strong competitiveness, but on the other hand, they do not have a strong comparative advantage. This is shown by the RCA value that less than 1. It means that a part of agricultural commodities, namely food crops, horticulture and estate, are still import oriented.